2016
DOI: 10.1590/s0100-204x2016001200012
|View full text |Cite
|
Sign up to set email alerts
|

Linhagens de frangos caipiras criadas em sistema semi-intensivo em região de clima quente

Abstract: Resumo -O objetivo deste trabalho foi avaliar o desempenho, as variáveis fisiológicas e o comportamento de cinco linhagens de frangos de corte caipiras criadas em sistema semi-intensivo, em região de clima quente. Utilizaram-se 400 aves, com idade inicial de 35 dias, em cinco tratamentos representados pelas linhagens caipiras: Pescoço Pelado, Vermelho Pesadão, Carijó, Master Griss e Colorido. Utilizou-se um delineamento inteiramente casualizado, com quatro repetições e 20 parcelas. Avaliaram-se desempenho (gan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
1
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 27 publications
3
1
0
2
Order By: Relevance
“…Regardless of the type of tile used, the physiological variables of the broilers did not differ (Table 2). Dias et al (2016), in a research on the evaluation of free-range chicken lines in the northern region of Minas Gerais reared in aviaries with fiber cement tiles, found higher rectal temperature values, but close to those of this study, with an average of 41.5 °C. According to the researched literature (Dionello et al 2002;Silva et al 2003;Nazareno et al 2011), the rectal temperature averages that characterize a comfort condition for broilers vary between 41 to 42 °C, values close to found in that work.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Regardless of the type of tile used, the physiological variables of the broilers did not differ (Table 2). Dias et al (2016), in a research on the evaluation of free-range chicken lines in the northern region of Minas Gerais reared in aviaries with fiber cement tiles, found higher rectal temperature values, but close to those of this study, with an average of 41.5 °C. According to the researched literature (Dionello et al 2002;Silva et al 2003;Nazareno et al 2011), the rectal temperature averages that characterize a comfort condition for broilers vary between 41 to 42 °C, values close to found in that work.…”
Section: Resultssupporting
confidence: 88%
“…Madeira et al (2010) in a study with birds of the Caipira Pesadão strain found values of weight gain and feed consumption different from those of this work being 3.21 kg and 10.76 kg, respectively, similarly to Castilho et al (2013) who obtained an average weight gain of 2.69 kg. However, Dias et al (2016) found values closer to that of this work for feed consumption (5.14 kg) and lower for feed conversion with an average of 2.94.…”
Section: Resultssupporting
confidence: 76%
“…Considerando lo anterior, la resistencia al calor constituye un factor importante en el desempeño productivo, ya que nuestro país presenta un clima tropical con temperaturas que pueden llegar a los 41 °C. En este sentido se puede mencionar el trabajo realizado por Nunes et al (10) en al año 2016 que, al someter a las aves de diferentes razas al estrés térmico, observaron mayor temperatura rectal en las aves de razas con plumajes completos en relación a aquellas con plumajes reducidos o de cuellos desnudos.…”
Section: Resultados Y Discusiónunclassified
“…These activities may justify the lower initial weight gain of the semi-confined birds. Nevertheless, these specific characteristics contribute to free-range chicken products' differentiated taste and quality (Dias et al, 2016).…”
Section: The Growth Pattern Of Brazilian Canela-preta Chickens With D...mentioning
confidence: 99%